What Haunts Pedagogical Documentation? Speculating With Data-Ghost(s) - Albin-Clark, Jo (Journal of Childhood Studies)

(untitled) (Canadian Association for Young Children, 2025)
With the imaginary of (a) data-ghost(s), I use ideas from hauntology to speculate about what haunts pedagogical documentation. By re-turning to an example of documentation of young children encountering a hatchery where eggs incubated into chicks, I notice the absences of what was not documented as hauntings. With performative and playful writing, I speculate with artworks and dialogue as a way of speaking of, to, and with ghosts. By thinking with the relationships between past/present/future, I ponder what inheritances, response-abilities, and possibilities emerge. Through slowing down with data-ghost(s), I speculate with what haunts and hauntings’ call for something-to-be-done to imagine what becomes possible for practices in the present and future for classroom practice and teacher education.